Al Wusail. Mesolitiske Flintpladser i Qatar - Nielsen, Viggo (Kuml, 1961)
The Al Wusail Mesolithic Flint Sites in Qatar. At several places along Qatar’s flat coast, isolated sections of rock rise as long ridges a short distance from the shore. Rock formations of this nature are found for example at Al Wakrah, Al Wusail, Jusasiyah al-Huwailah and Al Furihah, all marked on the map in Kuml 1957, p. 168. They are characterised by steep sides and an irregular surface with many depressions or long hollows. It cannot be mere coincidence that traces of Stone Age settlement have been found on or near many of these formations. They had several advantages to offer: outlook over an extensive game area and the sea, a certain amount of protection by virtue of the steep slopes, the possibility of shelter or concealment in the hollows and, at the foot of the rock, shelter from the winds. The Al Wusail ridge, fig. 2, was already known in 1957 as an important Stone Age site (Kuml 1957, p. 169 f.) and it was decided to undertake a closer investigation. This was completed in 1959, though not to the extent originally planned. The author, assisted for a while by Knud Dalgaard-Knudsen, managed to produce comprehensive flint material from several localities at Al Wusail. 12 localities were registered in 1959 on the basis of the surface concentration of flint. The ridge is situated on the east coast of Qatar about 25 km N. of the capital at Doha. It runs largely parallel to the shore at a distance of 6-700 m in a NNW-SSE direction. It is about 1 km long, 150-200 m across, and has a very irregular surface, the hollows running mainly longitudinally. Very near the rock, both N. and S. of it, are flat depressions that attract what little rain-water there is and have more vegetation than the rest of the desert. Under slightly more favourable climatic conditions these would have been attractive grazing areas for game or the habitat of bushes providing the material for arrow shafts. Locality 1 was in one of the irregular hollows, 30-40 m from the western edge of the rock. Worked flint was found in and on top of a 5-10 cm-thick layer of conglomerated gravel, beneath which a nearly stoneless, sterile layer of calcareous sand rested on the actual rock surface. The only more specialised pieces from the site were a 7 cm long unfinished tanged-point, where the percussion bulb had been removed by chipping from the keel side of the blade, and a broken triangular blade with retouche and marks of wear on the under side down one edge and on the keel side down the other. The location and patination of the flint indicate a surface find and its scarcity (2-3 per sq. m examined) rule out the locality as a true settlement. Locality 2 lies in an open stretch, up to 20 m wide of the same hollow as loc. 1. The absolutely horizontal surface (11.43 m above sea-level) consisted of hard conglomerate in which occasional pieces of worked, brown-patinated flint occurred. Under this was a loose layer of sand, 30-35 cm thick, with pockets of worked flint mostly towards the bottom, on or just above the wind-eroded rock surface. 61 sq. m. of the station were examined in all, comprising most of the flint concentrations, but the site was not exhausted when the work had to stop. The material from this locality showed no signs of having at any stage lain on the surface, being in contrast to surface flint light yellow or bleached brown, grey or sometimes red, with perfectly sharp edges. 5-6,000 pieces of flint, mostly waste, were collected. All implements were formed from blades or more or less irregular chips, so one can speak of a flake culture in the sense that core tools are absent. Flint blocks, judging by patination partly picked up on the desert surface, were the raw material of the flint-smith. The whole blocks or nodules are only 4.5-5.5 cm long and heavily worked, several having a roughly rectangular cross-section produced by flaking from ends and sides (pl. 11,1). It can be seen from one chip that the block could also approach cylindrical form. It appears also that the blocks could be considerably longer and otherwise prepared, as indicated by the occurrence of some 9-10 cm.-long chips from the edge of the block. 2 of these (one illustrated pl. II,8) show an extensive, very fine and regular, mainly one-sided edge-dressing, so they resemble, not least on account of their curved shape, axe-edge flakes. These chips are, then, a kind of keel blade. 5 other equally large chips are regular keel blades. A retouche-Iike dressing can also be seen on several short chips. The majority of chips which can safely be called blades (85), with their size of 4.5-6 cm. correspond to the scars on the small blocks. A few blades can on account of their size (c. 3 cm. long and 0.5 cm. across) be described as microblades, but none show signs of having been used. Generally, blades and chips are crude, thick and irregular, so the technique at this station is not advanced. Blades or blade-like chips are the basis of tool manufacture: knives, scrapers, arrowsmoothers etc., but first and foremost of the commonest and most specialised element, the tanged arrow-head. A total of 41 entire, broken or unfinished tanged-points were picked up from this locality. The entire, finished examples (pl. I) form the basis of the description of the group. All are fashioned from sharp, small blades or chips of normal size, their length varying between 3.4 and 5.7 cm. Chipping from both under- and keel-side have as a rule removed the percussion bulb completely and formed a narrow tang. The width of the tang measured just below the point where it joins the head, is about half that of the head itself, but this proportion is in a few instances (pl.I, 7 & 9) increased to 1:1.4. The tang normally lies on the medial axis but is in 4 cases displaced to one side. Of the entire examples, 3 have received only the primary dressing (pl. I, 1,3 & 4) whilst the remainder have an additional trimming of larger or smaller portions of point and blade. This is usually carried out from the under side, which thus is smooth from the root of the tang to the point (pl. 1,5-10 & 13) and only in 4 cases is the extreme tip worked from the keel side also and then mostly from the right (pl. 1, 2, 11, 12 & 14). In 4 instances only the point is trimmed but in 4 others the edge of the blade as far as the tang. The other specialised flint artifacts from this station are chipped or retouched on greater or smaller portions of the edges. 46 pieces of this nature were found and can be classified into several groups with differences that may have functional relevancy: a) 5 blades or chips are quite sharp at the percussion end, but broaden rapidly from there. They have a dressing showing marks of wear performed from the under side of the two long edges (pl. II, 2). b) 2 sturdy blades, 7 cm. in length, which taper towards the end, have a dressing of the whole long edge and notched portions suitable for arrow smoothing (pl. II, 6). 1 fragment belongs to the same type. c) 2 ordinary blade scrapers with dressing of the greatest part of the long sides, and convex termination (pl. II, 7). d) 5 "scythe-blade shaped" blades with retouching on the convex edge. The other edge has in several instances remains of the crust and has not been suited to cutting (pl. II, 5). e) 28 irregular chips and blades with edge-dressing of different kinds including notching for arrow sharpening or dentation well suited to stripping thin bark or the like (pl. Il, 4). f) 1 piece has the termination of the blade trimmed to a point. Must be described as a borer (pl. II, 9). g) 3 thick, coarse chips with preparation of a scraper edge on the convex ends (pl. II, 3). Locality 3 lay immediately S. of locality 2, but produced only a broken or unfinished tanged-point and 15 chips. Locality 4 was situated at the foot of the rock face, opposite a depression in the edge acting as a passage to the hollow that contained localities 1 and 2. Worked flint was found on the desert surface in a belt c. 50 m. long and 20-30 m. wide along the face of the ridge. The pieces collected (c. 100) included among other things 7 tanged points or bits of these and seem to be a manifestation of the comings and goings of the former inhabitants of the rock. Between the desert surface and the passage onto the cliff, a little 4 m. wide plateau was investigated. A layer of gravel 35 cm. thick produced 236 chips, besides some blocks, block chips and implements, concentrated below the cleft. The surface flint corresponded in every way to the inventory from loc. 2, whereas the buried pieces (light patina, sharp edges) differed, especially in the formation of the arrow-heads. The entire examples (pl. III, 4-5) are seen to have only a weak constriction towards the base, produced by chipping away the percussion bulb from the keel side. The tip itself is unworked. The pronounced indentations 1 cm. from the end can be for lashing. 1 broken arrow has the same character, while another from the surface (dark patina) has a pronounced tang worked from keel and under side. In addition, 7 blades, 1 stout flake scraper with convex edge (pl. III, 2), 4 blade scrapers with extensive retouche and marks of wear (pl. III, 3) and 1 blade with a number of notches in the edge, were found. Locality 4 cannot have seen any extensive habitation but must have been frequented by people living on the northern half of the ridge. Nevertheless two horizons can be distinguished; buried and surface flint. Locality 5 was a little hollow, 40 m. N. of loc. 2, and produced 1 blade scraper, a piece of an apparently surface-worked, leaf-shaped point and 2 chips. No worked flint was found on sieving the gravel. Locality 6, on the northern half of the ridge in a 20 m.-wide sand-filled depression was established on the basis of 12 chips and 1 broken piece of a tanged point, worked from both sides. Locality 7 was 40 m. N. W. of loc. 6 in a narrow, open space c. 20 m. long. Pieces of a blade scraper or blade point and 2 chips were found. Locality 8. A depression with access to a gap in the edge, yielding 30 pieces of waste flint and nothing on sieving. Locality 9, a little unprotected plateau, yielded a finely chipped arrow of Neolithic type (pl. III, 6) and 2 chips. Locality 10 lay on a plateau about 400 m. further N. 9 chips, 1 block and 2 flake scrapers, all brown patinated, were picked up superficially, and an additional 28 chips on sieving 8 sq. m. of the 20 cm. sand layer. Locality 11 was situated in a narrow hollow containing a layer of gravel up to 15 cm. thick. It was opposite another cleft in the face which gave good access. 103 pieces of flint, including 2 fragments of tanged points were found superficially. Sieving produced, apart from 866 chips, a number of more specialised pieces. 13 blocks or nodules showed signs of roughing, although they are somewhat larger than the blocks from loc. 2. 2 reach 6 cm. (pl. V, 2), 2 others only 3.5 cm. (pl. V, 3). The relatively irregular flaking is also here performed from ends and sides. Also among the 28 true blades are examples which, with a length of 8.5 cm. exceed the size of those from loc. 2. 10 arrow-heads, of which only 3 were entire, the remainder unfinished or fragments, had been worked from blades. This group can hardly be called tanged points as the only sign of a tang is a weak constriction (pl. IV, 1-3). The percussion end is rounded and the bulb removed by flaking from the keel side. Only 2 of the 10 show a few marks of retouching on the keel side. A quite special form of arrow-head has been developed from a 9 cm. chip off the edge of a very carefully dressed block or flake, the percussion bulb having been removed by chipping from the keel side. The find includes 19 other chips from blocks prepared on one side only, besides 3 keel blades where both sides of the keel have transverse flaking (pl. IV, 7). The smaller blade- or flake-tools from the other localities turn up here too, the blades with retouched edges with notches for smoothing or tearing (pl. IV, 4). Unique is a relatively sturdy blade, the base of which has been worked to a tang just like that of the blade points, by chipping away of the percussion bulb, while the other end has a convex scraper edge (pl. IV, 6). There is no basis of comparison for deciding whether this is a true type or a mere curiosity. 8 scrapers are fashioned from such thick and coarse chips that the retouching appears steep (pl. V, 1). These are sturdier than their counterparts from loc. 2. Locality 12 lies in a cleft down the side of the rock opposite loc. 11. 42 pieces of surface flint were collected, including 2 blocks, some block-edge chips and a solitary blade with signs of wear and concave retouche. There was no opportunity for a further examination. Of the localities on the A1 Wusail ridge, only 2, 4, 8, 10, 11 and 12 have such a large content of worked flint that it is reasonable to describe them as habitation sites. These 6 localities are separated from one another by distance, rock-edges, etc., to such an extent that they, with reserve where 4 and 12 are concerned, which lie in or below clefts, can be considered independent temporary or permanent habitation-sites, without implying that they are automatically from different periods. The material from loc. 2, in view of its content and configuration, constitutes a unit, primarily distinguished by a special development of the tanged points. Locality 4 shows possibly 2 horizons, the surface- and the buried flint, of which the surface flint corresponds exactly to locality 2 material, whereas the rest has a more primitive stamp and resembles more the comprehensive and apparently integral material from loc. 11. Although the inventory in 2 and 11 is roughly equivalent, 11 has a bolder character, especially in the case of the arrow-heads. Localities 8, 10 and 12 lack sufficient representative material for a true estimate of relationships. It thus appears that in Qatar’s Stone Age, at a time when hunting culture dominated with an inventory corresponding to other areas’ mesolithic, 2 groups or phases can be distinguished inside a quite uniform group. Closer examination of the ridge might yield a station corresponding to the single neolithic-type ,arrow-head found, and cast further light on development. The Al Wusail finds are locally isolated, far from the nearest areas where other groups have used corresponding forms of the main type-the tanged point-for example to Egypt’s Tahunian or to Iraq. Neither are parallels forthcoming from Qatar, and material from other rock formations on the peninsula is not comprehensive enough for any conclusions to be drawn. Those blocks found in 1959 beneath the Al Wakrah-rock, S. of Doha, correspond, however, to those from Al Wusail. The only basis for placing Al Wusail chronologically, is a general impression of the tool inventory, as belonging to a Mesolithic milieu. Viggo Nielsen.